Association between hospital volume, processes of care and outcomes after acute ischaemic stroke: a prospective observational study - Yongjun Wang; Maigeng Zhou; Gaifen Liu; Yuesong Pan; Runhua Zhang (BMJ Open, 2022)
Objectives There is uncertainty with respect to the hospital volume and clinical outcomes for patients with stroke. This study aimed to assess the association between hospital volume, processes of care and outcomes after ischaemic stroke.Design A multicentre prospective cohort study.Setting Two hundred and seventeen secondary or tertiary public hospitals from China.Participants A total of 17 550 patients within 7 days of acute ischaemic stroke were included.Main outcome measures The outcomes included all-cause mortality, poor outcome, recurrent stroke, and combined vascular events at 3 months and 1 year. The patients were divided into four groups based on quartiles of the hospital volume. We compared the difference in the process of care across the groups and estimated the effects of hospital volume on mortality, poor outcome, recurrent stroke, and combined vascular events at 3 months and 1 year. Restricted cubic splines were used to illustrate the association between hospital volume and clinical outcomes.Results There were no significant differences in the process of care across the four groups. When adjusted for confounders, the effect of hospital volume on mortality, recurrent stroke and combined vascular events was not significant. However, compared with the highest quartile, the patients in the lowest quartile of hospital volume tend to have poor outcome at 1 year (OR=1.29, 95% CI 1.01 to 1.64, p=0.0393). The restricted cubic spline analyses suggested a non-linear relationship between hospital volume and 1-year combined vascular events and poor outcome at 3 months and 1 year.Conclusions We found no significant associations between hospital volume, processes of care at the hospital, and mortality, recurrent stroke, and combined vascular events in patients with ischaemic stroke. However, hospital volume may be associated with poor outcome at 1 year.